Family-of-origin factors and teen dating violence victimization and perpetration: a meta-analysis - Emanuels, Sarah K. (Kansas State University, 2019)
Teen dating violence (TDV) is a common problem among adolescents, yet little is known about the risk markers for TDV perpetration and victimization. The purpose of this meta-analysis was to explore the relationship between family-of-origin factors (i.e., attachment, witnessing inter-parental violence, experiencing abuse as a child, poor parenting, and parental support) and TDV victimization and perpetration. A total of 27 studies, which yielded 81 effect sizes examining physical TDV perpetration and victimization, were included in the study. Results from our analysis revealed that anxious attachment was the strongest risk marker for TDV perpetration and experiencing abuse as a child was the strongest risk marker for TDV victimization. Our results also revealed that witnessing inter-parental violence was a significant risk marker for TDV perpetration and victimization, poor parenting was a significant risk marker for TDV victimization, avoidant attachment and experiencing abuse as a child were significant risk markers for perpetration, and parental support was a significant protective marker against TDV victimization. These findings highlight the importance of family factors when identifying adolescents who are at risk for TDV, as well as developing violence prevention and intervention programs.
Keywords: Teen dating violence; Family-of-Origin; Meta-Analysis; Adolescent